2012
DOI: 10.1504/ijtel.2012.051818
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning in context

Abstract: The widespread use of mobile technologies has led to an increasing interest in mobile learning. Context is a central topic of research in that area. In fact, a major benefit of mobile devices is that they enable learning across contexts. In this paper, we explore how context can deliver significant benefits in mobile learning and provide an extensive review of the current literature and research on mobile learning in context. Furthermore, we identify various challenges and research opportunities in this area a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 39 publications
0
9
0
5
Order By: Relevance
“…Context may contain information about the current situation, in which the learner is in, her pace, knowledge, interest, peers, motivation, etc. This knowledge enables applications to present only those parts of the learning activity that are of interest in that special situation [11]. Context-aware mobile learning systems can adapt to every situation, give intelligent feedback to the preceding learning process, and produce recommendations for new learning items or activities.…”
Section: Mobile Learning In Contextmentioning
confidence: 99%
“…Context may contain information about the current situation, in which the learner is in, her pace, knowledge, interest, peers, motivation, etc. This knowledge enables applications to present only those parts of the learning activity that are of interest in that special situation [11]. Context-aware mobile learning systems can adapt to every situation, give intelligent feedback to the preceding learning process, and produce recommendations for new learning items or activities.…”
Section: Mobile Learning In Contextmentioning
confidence: 99%
“…CAMeL, context-aware mobile learning, es un prototipo para investigar cómo aprovechar el contexto para proponer información y actividades de aprendizaje específicas y orientadas al momento y entorno mediante el dispositivo móvil (Thüs et al, 2012).…”
Section: Detección De Actividades Y Control De Interrupcionesunclassified
“…In this context, reports like the one from UNESCO (West & Vosloo, 2013) has shown that mobile technology provides opportunities for learners to engage in a broader range of informal learning activities, especially to make learners responsible for executing learning actions. Mobile technology provides opportunities for more personalized and autonomous seamless experiences across learning contexts (Thüs et al, 2012), in which learners have freedom and power to make proactive decisions. Sharples, Taylor, Vavoula (2007) suggested that learners' agency lies in a socio-cultural synergy between all the individuals willing to advance knowing, instead of relying on the individual learner.…”
Section: Introductionmentioning
confidence: 99%